British women surgeons and their patients, 1860 -1918 - Brock, Claire, 1977- (Cambridge : Cambridge University Press, 2017)
When women agitated to join the medical profession in Britain during the 1860s, the practice of surgery proved both a help (women were neat, patient and used to needlework) and a hindrance (surgery was brutal, bloody and distinctly unfeminine). In this major new study, Claire Brock examines the cultural, social and self-representation of the woman surgeon from the second half of the nineteenth century until the end of the Great War. Drawing on a rich archive of British hospital records, she investigates precisely what surgery women performed and how these procedures affected their personal and professional reputation, as well as the reactions of their patients to these new phenomena. Essential reading for those interested in the history of medicine, British Women Surgeons and their Patients, 1860-1918 provides wide-ranging new perspectives on patient narratives and women's participation in surgery between 1860 and 1918. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 20 Mar 2017).
Keywords: Women surgeons -- Great Britain -- History -- 19th century; Women surgeons -- Great Britain -- History -- 20th century; Women physicians -- Great Britain -- History -- 19th century; Women physicians -- Great Britain -- History -- 20th century; World War, 1914-1918 -- Medical care; World War, 1914-1918 -- Women